(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Monitoring of Bosso dam by integrating geoscientific principles was executed. The dam was constructed in 1949 to provide fresh water for human consumption. Physical deterioration, evidence by structure material wear out, concrete cracks and mechanical equipment worn-out among others are visible on the dam and its appurtenant structure. The basement rocks underlying the dam area are weathered and fractured as evidence on the outcrops within the proximity of the dam. Geotechnical characteristics of soil obtained from the dam site includes: Liquid limit range of 30% - 35%, plastic limit range of 26% - 38% and Plasticity index range of 4% to 15%. The classes of the soils fall within the MI, MH and ML soil categories of the USCS, indicating silt of medium, high and low plasticitys. VES models show 3 geoelectric layers which includes regolith/organic silts layer with average resistivity value 50 m. The 2nd layer shows a resistivity range of 9 m to 43 m to the depth range of 3.3m to 4.7m. The 3rd layer is composed of silty-clay and saprolite with resistivity of 163 m. From the 2D tomography, the low resistivity anomalous noticed at the western section of the dam embankment toe is attributed to the effect of possible seepage caused by internal erosion. The effect of ageing and global warming has led to safety deficiencies of Bosso dam that were not apparent at commissioning until recently, therefore urgent remedial measures are needed for the safety of the dam.